Indonesian engineers, the free nutritious meal program (MBG) needs you! - Muji Setiyo (Universitas Muhammadiyah Magelang, 2026)
Indonesia's Free Nutrition Meal Program (Makan Bergizi Gratis, MBG), launched in January 2025, is a national social policy designed to improve the nutritional quality of schoolchildren and strengthen social justice. However, in the early stages of implementation, various obstacles such as uneven distribution of services, lack of standard operating procedures, weak supervision, and cases of food poisoning indicate systemic vulnerabilities in kitchen operations. MBG kitchens are not home-scale kitchens, but rather industrial-scale food production facilities that handle perishable food under high time pressure. Therefore, food quality control and safety cannot be adequately addressed through human resource management and training alone but require the integration of engineering into system design and control. In response to these concerns, this editorial calls for the involvement of interdisciplinary engineers to provide evidence-based critique and input on the standardization and sustainability of MBG kitchens. Several engineering needs have been identified, including energy-efficient hot water systems, cold chains, tableware sterilization, ventilation, ergonomic layouts, wastewater management, water recovery, modular kitchens for remote areas, conveyor-based washing automation, and remote process monitoring and recording. In addition, the involvement of engineers and professional associations is essential in formulating and refining evidence-based policies to optimize implementation, while also reducing risks during MBG operations.